Pendidikan Multikultural (Multicultural Education) Melalui Hadis - Khairin Nazmi; M. Fajri Yusuf; Muhammad Nuh Siregar (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Islam teaches the importance of tolerance and peace between individuals, whether they are of the same religion or those of different religions. Multiculturalism is a topic that is increasingly being discussed lately. Increased interest in the issue of multiculturalism is in line with progress in education that is free from restrictions. Multiculturalism education can help individuals to appreciate differences with a high level of tolerance, which is in accordance with Islamic values ​​in social interactions in society. Through this education, students can strengthen their personal character and find an identity that is consistent with their knowledge, especially in Islamic Religious Education, which emphasizes the main characteristics of Muslim behavior.